DIVERSITY OF ENDOPHYTIC BACTERIA ASSOCIATED WITH (Curcuma heyneana) AND THEIR POTENCY FOR NITROGEN FIXATION - Tri Ratna Sulistiyani; Puspita Lisdiyanti (Pusbindiklat - LIPI, 2016)
Endophytic bacteria shows a high biodiversity and some of the species plays important biological roles in agriculture. The aim of this study was to investigate the endophytic bacteria diversity associated with temu giring (Curcuma heyneana) and to evaluate its nitrogen-fixation activity. Temu giring was collected from Bogor Botanic Garden. The isolation of endophytic bacteria was carried out using two methods (spread plate and plant piece methods) and four different medias (Nutrient Agar (NA), NA contained temu giring extract (NAH), Water Yeast Extract Agar (WYEA), and WYEA contained temu giring extract (WYEAH)). The identification of selected isolates were conducted based on 16S rDNA. The ability of selected isolates to fix the nitrogen on Jensen’s media is then being tested. The results revealed that the suitable method and media of endophytic bacteria isolation were spread plate method and NA. Based on the morphological characteristics differentiation, 30 isolates were obtained from rhizome (27%), stem (50%), and leaves (23%). The sequencing result of 16S rDNA showed that community of endophytic bacteria was divided into six clusters, those are Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Flavobacteriia, Actinobacteria, and Firmicutes,which represented 17 genus consisted of Microbacterium, Leclercia, Brevundimonas, Chromobacterium, Enterobacter, Acinetobacter, Novosphingobium, Chryseobacterium, Curtobacterium, Agrobacterium, Sphingomonas, Herbaspirillium, Bacillus, Variovorax, Mycobacterium, Starkeya, and Rhizobium. A total of eleven isolates could grow in the N free medium. The presence of endophytic bacteria those were able to fix nitrogen are expected to be applied in agricultural sector as a biological fertilizer.